The famous five (five go to Billycock Hill) - Blyton, Enid; Eileen Alice Soper (Great Britian Hodder and Stoughton, 1997)
The Famous Five have made a new friend -- a pilot! But he has disappeared with top secret equipment. The Five can't believe it -- is Jeff a traitor?